Value-based healthcare analysis of shoulder surgery for patients with symptomatic rotator cuff tears – Calculating the impact of arthroscopic cuff repair. (July 2022) - Holzer-Fleming, C; Tavakkolizadeh, A; Sinha, J; Casey, J; Moxham, J; Colegate-Stone, Toby J
Background: Surgical repair of full-thickness rotator cuff tears in symptomatic patients is known to offer significant benefits. Despite this there remains a lack of universal appreciation that such surgery offers high clinical value, with some commissioners even limiting access to it. The value-based healthcare agenda provides a means to design, deliver and measure the impact of healthcare to a defined segment of patients. The aim of this study was to measure the value of surgically repairing primary symptomatic full-thickness rotator cuff tears when outcomes and costs were assessed over an entire care pathway. Methods: A prospective study of patients undergoing rotator cuff tears repair was undertaken. Patients were managed using a standardised integrated care pathway. Subsequent outcomes and costs were measured over the whole care pathway. Outcomes were assessed from both traditional and patient centric re-formatted prisms. Results: Significant improvement in clinical outcomes where recognised when assessed from either the traditional or re-formatted prisms. Economic review of this approach revealed the pathway generated a sustainable and notable positive margin. Discussion: This study evidences how a well-designed value-based healthcare shoulder approach can be delivered and measured. It demonstrates rotator cuff surgery to be a high value treatment for patients with symptomatic rotator cuff tears.